Modified carbon nanofiber as well as preparation method and application thereof
The carbon nanofibers prepared and modified through electrospinning technology have solved the problem of poor hydrophilicity and electrochemical performance of existing carbon nanofibers in all-vana flow batteries, and achieved a significant improvement in battery energy density and cyclic stability.
Patent Information
- Application Number
- CN202411657371.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing carbon nanofibers show poor hydrophilicity and electrochemical performance in all vanadium flow batteries, which is difficult to meet the requirements of the development of flow batteries.
Electrospinning nanofibers were prepared by electrospinning technology, and pre-oxidized and graphitized. Then, using K2FeO4 solution for soaking and calcining to form an etchant and catalyst, and finally acidification was carried out to obtain oxygen-rich, porous, and highly graphitized modified carbon nanofibers.
Modified carbon nanofibers significantly improve the energy density and cycle stability of the battery, provide better conductivity and hydrophilicity, and are suitable for all-vanadium liquid flow battery electrode materials.
Smart Images

Figure CN119507196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and electrochemical technology, and in particular to a modified carbon nanofiber, a preparation method and application thereof. Background Art
[0002] All-vanadium redox flow batteries have attracted widespread attention due to their long life, high energy efficiency and environmental friendliness. The performance of electrode materials, as the core component, seriously affects the comprehensive energy storage performance of all-vanadium redox flow batteries. Therefore, the research, development and utilization of electrode materials are the key to the large-scale commercial promotion and application of vanadium batteries.
[0003] At present, the electrode materials used in vanadium batteries mainly include metal materials and carbon-based materials. Among them, metal electrodes are often expensive and difficult to use in large-scale commercial applications of vanadium batteries, while carbon-based materials such as glassy carbon electrodes have poor electrochemical reversibility for vanadium electrodes; graphite electrodes have obvious etching phenomena after multiple cycles; the original graphite felt material has problems such as poor electrochemical activity and hydrophilicity, and often needs to be modified before use. Therefore, finding an electrode material with better performance is of great significance for the large-scale commercial application of vanadium batteries.
[0004] In recent years, carbon nanofibers have been widely used as electrode materials for all-vanadium flow batteries due to their large specific surface area and good conductivity. However, conventional carbon nanofiber materials often lack many surface catalytic properties, resulting in their hydrophilicity, electrochemical activity and reversibility being difficult to meet the requirements of flow battery development. Therefore, research on the modification of carbon nanofibers has become a hot topic in the field of electrochemical energy storage. Summary of the invention
[0005] The main purpose of the present invention is to provide a modified carbon nanofiber, a preparation method and application thereof, so as to solve the problem of poor hydrophilicity and electrochemical performance of carbon nanofibers in the prior art.
[0006] In order to achieve the above-mentioned object, according to the first aspect of the present invention, a method for preparing modified carbon nanofibers is provided, the method comprising: S1, dissolving polyacrylonitrile in N,N-dimethylformamide to obtain an electrospinning precursor solution; S2, subjecting the electrospinning precursor solution to electrospinning treatment to obtain an electrospinning nanofiber material; S3, sequentially subjecting the electrospinning nanofiber material to pre-oxidation and graphitization treatment to obtain unmodified carbon nanofibers; S4, using K 2 FeO 4 After the unmodified carbon nanofibers are soaked in the solution, first drying, calcination and acidification treatment are performed in sequence to obtain modified carbon nanofibers.
[0007] Furthermore, the mass fraction of polyacrylonitrile in the electrospinning precursor solution is 5-15%; preferably, the dissolution temperature is 50-80° C.; preferably, the dissolution time is 2-5 hours; preferably, the relative molecular mass of polyacrylonitrile is 50,000-200,000.
[0008] Furthermore, the electrospinning process includes: sucking the electrospinning precursor solution into a syringe, and performing electrospinning on an aluminum foil attached to a metal plate through the syringe; preferably, the inner diameter of the needle of the syringe is 0.1-1.0 mm; preferably, the propulsion speed of the syringe is 0.1-1.0 mL / h; preferably, the receiving vertical distance of the electrospinning is 5-15 cm; preferably, the voltage of the electrospinning is 10-18 kV.
[0009] Further, S3 includes: before pre-oxidation, the electrospun nanofiber material is first vacuum-dried and then pre-oxidized in an air atmosphere; preferably, the vacuum drying temperature is 50-90°C; preferably, the vacuum drying time is 6-24h; preferably, the vacuum degree of vacuum drying is 0.05-0.1Mpa; preferably, the pre-oxidation temperature is 240-280°C; preferably, the pre-oxidation time is 1-3h.
[0010] Further, graphitization is carried out in an argon atmosphere; preferably, the temperature is raised to the graphitization temperature at a rate of 2-5°C / min; preferably, the graphitization temperature is 700-1000°C; preferably, the graphitization time is 2-3h.
[0011] Furthermore, unmodified carbon nanofibers and K 2 FeO 4 The mass ratio of K is 1:1-5; preferably, the unmodified carbon nanofibers are immersed in K 2 FeO 4 The time in the solution is 12-24h; preferably, the temperature of the first drying is 60-90°C; preferably, calcination is carried out in an argon atmosphere; preferably, the temperature is increased to the calcination temperature at a rate of 2-5°C / min; preferably, the calcination temperature is 700-1000°C; preferably, the calcination time is 2-3h.
[0012] Furthermore, the reagent for the acidification treatment includes a dilute hydrochloric acid solution; preferably, the concentration of the dilute hydrochloric acid solution is 0.5-1.5 mol / L; preferably, after the acidification treatment, filtering, washing and second drying are performed in sequence to obtain modified carbon nanofibers.
[0013] In order to achieve the above object, according to a second aspect of the present invention, a modified carbon nanofiber obtained by the above preparation method is provided.
[0014] In order to achieve the above-mentioned purpose, according to the third aspect of the present invention, there is provided an application of the modified carbon nanofibers obtained by the above-mentioned preparation method in the electrode material of the all-vanadium liquid flow battery, and the application comprises: dispersing the modified carbon nanofibers in N,N-dimethylformamide by ultrasonic treatment to obtain a modified carbon nanofiber dispersion; coating the modified carbon nanofiber dispersion on a glassy carbon electrode and drying it to obtain the electrode material of the all-vanadium liquid flow battery.
[0015] Furthermore, the ultrasonic treatment time is 1-5h; preferably, the concentration of modified carbon nanofibers in the modified carbon nanofiber dispersion is 2-5mg / mL; preferably, the volume of modified carbon nanofiber dispersion for coating is 20-80mL; preferably, the drying temperature is 60-90°C; preferably, the drying time is 6-24h.
[0016] By applying the technical solution of the present invention, the electrospun nanofibers are pre-oxidized and graphitized to obtain unmodified carbon nanofibers, and then immersed in K 2 FeO 4 In solution, K adsorbed onto the unmodified carbon nanofibers 2 FeO 4 After high-temperature calcination and decomposition, KOH (etchant) and Fe (catalyst) are formed, which can simultaneously realize the activation etching and catalytic graphitization of carbon nanofibers. Finally, after acidification treatment, oxygen-rich, porous, and highly graphitized carbon nanofibers are obtained. The carbon nanofibers have more active sites, high specific surface area, good conductivity and hydrophilicity. When used as electrode materials, they can significantly improve the energy density and cycle stability of batteries, and can provide strong technical support for the development of new energy fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic diagram of the process of preparing modified carbon nanofibers from electrospun nanofibers in the present application is shown.
[0019] Figure 2 The results show that the different K 2 FeO 4 The effect of dosage on the morphology of the prepared carbon nanofibers; wherein, Figure 2 (a) is the SEM image of the unmodified carbon nanofiber (CNF) obtained in Example 1, Figure 2 (b) is the SEM image of the carbon nanofiber (CNF-PF-1) obtained in Example 1. Figure 2 (c) is the SEM spectrum of the carbon nanofiber (CNF-PF-3) obtained in Example 2. Figure 2 (d) is the SEM image of the carbon nanofiber (CNF-PF-5) obtained in Example 3. Figure 2 (e) is the SEM spectrum of the carbon nanofiber (CNF-P-F1) obtained in Comparative Example 1. Figure 2 (f) is the SEM image of the carbon nanofiber (CNF-P-F2) obtained in Comparative Example 2.
[0020] Figure 3 The XRD spectrum results of analyzing the phase composition of the products (CNF, iron-carbon mixture and CNF-PF-3) obtained in the preparation process of Example 2 using an X-ray diffractometer are shown.
[0021] Figure 4 The XPS full spectrum of CNF and CNF-PF-3 obtained in Example 2 is shown by X-ray photoelectron spectroscopy (XPS) analysis ( Figure 4 (a) in the figure), and the C1s high-resolution XPS spectra of CNF and CNF-PF-3 ( Figure 4 (b) and (c) in Figure 5.
[0022] Figure 5 The contact angles of CNF and CNF-PF-3 obtained in Example 2 measured by a contact angle meter (JC2000D1) using a baseline ring method are shown.
[0023] Figure 6 The N of CNF and CNF-PF-3 obtained in Example 2 is shown. 2 Isothermal adsorption-desorption curve ( Figure 6 (a) in the figure, and the transmission electron microscopy image of CNF ( Figure 6 (b) in the figure.
[0024] Figure 7 The specific surface area and pore size distribution of the CNF and CNF-PF-3 obtained in Example 2 are analyzed using a specific surface area pore size analyzer ( Figure 7 (a) in the figure, and the transmission electron microscopy image of CNF-PF-3 ( Figure 7 (b) in the figure.
[0025] Figure 8 The glassy carbon electrode modified with CNF and CNF-PF-1 prepared in Example 1, the glassy carbon electrode modified with CNF-PF-3 prepared in Example 2, the glassy carbon electrode modified with CNF-PF-5 prepared in Example 3, and the blank glassy carbon electrode (GCE) at 1.6 mol / LV 3++3.0mol / LH 2 SO 4 CV curves at a scan rate of 5 mV / s in electrolyte ( Figure 8 (a)), the CNF-PF-3 modified glassy carbon electrode prepared in Examples 2, 4 and 5 was 1.6 mol / LV 3+ +3.0mol / LH 2 SO 4 CV curves at a scan rate of 5 mV / s in electrolyte ( Figure 8 (b)), the electrochemical impedance spectroscopy (EIS) spectra of the CNF-modified glassy carbon electrode prepared in Example 1 and the CNF-PF-3-modified glassy carbon electrode prepared in Example 2 ( Figure 8 (c) in the figure.
[0026] Fig. 9 The test results of charging and discharging of batteries assembled with CNF prepared in Example 1 and CNF-PF-3 electrodes prepared in Example 2 on a blue battery test system (CT3002A) are shown; Fig. 9 (a) is the result diagram of discharge capacity. Fig. 9 (b) in the figure is the result diagram of energy efficiency.
[0027] Fig.10 The charge and discharge curves of a battery assembled using CNF-PF-3, CNF-PF-7 or CNF-PF-9 prepared in Examples 2, 4 and 5 for both positive and negative electrodes and CNF-P-F1 prepared in Comparative Example 1 for both positive and negative electrodes on a blue battery test system (CT3002A) are shown. DETAILED DESCRIPTION
[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0029] As mentioned in the background technology, the pore size, structure and composition distribution of carbon nanofibers have a great influence on their hydrophilicity and electrical conductivity. However, although commonly used heat treatment and acid treatment techniques increase the surface roughness of carbon nanofiber materials, the effect of increasing their specific surface area is often limited, resulting in the increase in charge transfer rate and the decrease in diffusion resistance not meeting the requirements of flow battery electrode materials. Therefore, the present application intends to provide a modified carbon nanofiber and a preparation method thereof to improve the hydrophilicity, surface electrochemical activity and electrical conductivity of carbon nanofibers.
[0030] In a first typical embodiment of the present application, a method for preparing carbon nanofibers and modified electrodes is provided, the preparation method comprising: S1, dissolving polyacrylonitrile in N,N-dimethylformamide to obtain an electrospinning precursor solution; S2, electrospinning the electrospinning precursor solution to obtain an electrospinning nanofiber; S3, pre-oxidizing and graphitizing the electrospinning nanofiber in sequence to obtain unmodified carbon nanofibers; S4, using K 2 FeO 4 After the unmodified carbon nanofibers are soaked in the solution, first drying, calcination and acidification treatment are performed in sequence to obtain modified carbon nanofibers.
[0031] Among them, Figure 1 The reaction process shown in the figure shows that the structure of the electrospun nanofiber material of the present application is a chain of polyacrylonitrile. After the electrospun nanofiber material is pre-oxidized and graphitized, unmodified carbon nanofibers are obtained. The structure of the unmodified carbon nanofiber is an amorphous oxygen-containing carbon ring. The unmodified carbon nanofiber is immersed in K 2 FeO 4 , and high temperature calcination, K 2 FeO 4 Decomposed to form KOH (etchant) and Fe (catalyst), which can simultaneously achieve activation etching of carbon nanofibers and further catalytic graphitization. 2 FeO 4 Electrospinning nanofibers is a gentle and controllable process that will not damage the main structure of the carbon nanofibers and is beneficial to the modification of the carbon nanofibers.
[0032] On the one hand, KOH on the surface of unmodified carbon nanofibers reacts with C after calcination to produce a compound of K and K (K 2 O), followed by K and K 2 O will etch the unmodified carbon nanofibers through physical and chemical effects, so that the modified carbon nanofibers form a larger microporous structure and increase its specific surface area. In addition, KOH activation etching introduces abundant oxygen-containing groups into the modified carbon nanofibers, which can improve the hydrophilicity of the carbon nanofibers and provide more active sites for redox reactions, thereby accelerating the electrode reaction of the modified carbon nanofibers.
[0033] On the other hand, Fe(OH) 3 Calcination gradually converts into iron oxide (Fe 2 O 3 and Fe 3 O 4) and metallic Fe, and Fe can be used as a catalyst to convert amorphous carbon into graphite carbon, thereby completing the further graphitization of unmodified carbon nanofibers to improve the conductivity of modified carbon nanofibers. The calcined carbon nanofibers are then acidified to remove the residual iron and iron-based compounds, and modified carbon nanofibers with good hydrophilicity, large specific surface area and high degree of graphitization can be obtained. They can be used as electrode materials to provide a good channel for the electrolyte to infiltrate its electrode surface, accelerate the charge transfer at the electrolyte electrode interface, thereby improving the electrochemical performance of the battery, and can be used in many energy storage fields such as renewable energy storage, power grid peak regulation, and emergency power supply.
[0034] In order to further ensure that polyacrylonitrile is fully dissolved to form a uniform precursor solution, in a preferred embodiment, the mass fraction of polyacrylonitrile in the electrospinning precursor solution is 5-15%; preferably, the dissolution temperature is 50-80°C; preferably, the dissolution time is 2-5h; preferably, the relative molecular mass of polyacrylonitrile is 50000-200000; preferably, the stirring form is magnetic stirring.
[0035] In order to further effectively control the electrospinning process, prepare modified carbon nanofibers with high aspect ratio, large specific surface area, good adsorption characteristics and surface chemical activity, so as to further improve the cyclic stability of the modified carbon nanofibers, in a preferred embodiment, the electrospinning process includes: sucking the electrospinning precursor solution into a syringe, and electrospinning on an aluminum foil attached to a metal plate through the syringe; preferably, the inner diameter of the needle of the syringe is 0.1-1.0mm; preferably, the propulsion speed of the syringe is 0.1-1.0mL / h; preferably, the receiving vertical distance of the electrospinning is 5-15cm; preferably, the voltage of the electrospinning is 10-18kV.
[0036] In order to further fix the morphology of the electrospun nanofibers, in a preferred embodiment, S3 includes: before pre-oxidation, the electrospun nanofibers are first vacuum-dried and then pre-oxidized in an air atmosphere; preferably, the vacuum drying temperature is 50-90°C; preferably, the vacuum drying time is 6-24h; preferably, the vacuum degree of vacuum drying is 0.05-0.1Mpa; preferably, the pre-oxidation temperature is 240-280°C; preferably, the pre-oxidation time is 1-3h.
[0037] In order to further improve the conductive properties of the electrospun nanofibers, they are calcined in an inert gas atmosphere to increase their degree of graphitization. In a preferred embodiment, graphitization is carried out in an argon atmosphere; preferably, the temperature is raised to the graphitization temperature at a rate of 2-5°C / min; preferably, the graphitization temperature is 700-1000°C; preferably, the graphitization time is 2-3h.
[0038] In order to improve the ion diffusion and adsorption rate, charge transfer and electron transmission rate of amorphous carbon nanofibers, the prepared amorphous carbon nanofibers were modified and K 2 FeO 4 After soaking, drying, and then chemically etching by high temperature calcination, the carbon nanofiber surface has an etched porous structure, and the oxygen-containing and graphitization degree of the carbon nanofiber are further improved, which not only improves the hydrophilicity and charge transfer rate of the carbon nanofiber, but also reduces the charge transfer diffusion resistance. In order to further obtain carbon nanofibers with uniform pore distribution and high graphitization degree, in a preferred embodiment, the unmodified carbon nanofiber and K 2 FeO 4 The mass ratio of K is 1:1-5; preferably, the unmodified carbon nanofibers are immersed in K 2 FeO 4 The time is 12-24h; preferably, the temperature of the first drying is 60-90°C; preferably, the calcination is carried out in an argon atmosphere; preferably, the temperature is raised to the calcination temperature at a rate of 2-5°C / min; preferably, the calcination temperature is 700-1000°C; preferably, the calcination time is 2-3h.
[0039] In order to further obtain oxygen-rich, porous, highly graphitized carbon nanofibers to remove residual iron and iron-based compounds, in a preferred embodiment, the reagent for acidification treatment includes a dilute hydrochloric acid solution; preferably, the concentration of the dilute hydrochloric acid solution is 0.5-1.5 mol / L; preferably, after the acidification treatment, filtration, washing and drying are carried out in sequence to obtain modified carbon nanofibers.
[0040] In a second typical embodiment of the present application, a modified carbon nanofiber obtained by the above-mentioned preparation method is provided.
[0041] In a third typical embodiment of the present application, there is provided an application of a modified carbon nanofiber electrode obtained by the above-mentioned preparation method in an all-vanadium liquid flow battery electrode material, the application comprising: dispersing the modified carbon nanofiber in N,N-dimethylformamide by ultrasonic treatment to obtain a modified carbon nanofiber dispersion; coating the modified carbon nanofiber dispersion on a glassy carbon electrode and drying it to obtain an all-vanadium liquid flow battery electrode material.
[0042] In order to further improve the performance of the obtained all-vanadium liquid flow battery electrode material, in a preferred embodiment, the ultrasonic treatment time is 1-5h; preferably, the concentration of the modified carbon nanofibers in the modified carbon nanofiber dispersion is 2-5mg / mL; preferably, the volume of the modified carbon nanofiber dispersion for coating is 20-80mL; preferably, the drying temperature is 60-90°C; preferably, the drying time is 6-24h.
[0043] The application of this modified carbon nanofiber as an electrode material can significantly improve the performance of the battery, making it show great potential in a wide range of fields such as energy storage systems, drones, mobile devices, wearable devices, portable electronic products, high-performance batteries, supercapacitors, aerospace, precision instruments, laboratory equipment, etc., providing strong support for promoting the development of energy technology and realizing the use of green and sustainable energy.
[0044] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0045] Embodiment 1
[0046] S1, preparation of electrospinning precursor solution: weigh 10g polyacrylonitrile (PAN, relative molecular mass 85000) in a 250mL beaker, add 100mL N,N-dimethylformamide (DMF). Place the mixed solution in a constant temperature magnetic stirrer (80℃) and stir for 4h to obtain an electrospinning precursor solution with a mass fraction of 9.54% polyacrylonitrile and uniform viscosity.
[0047] S2, preparation of electrospun nanofibers: electrospinning nanofibers were prepared by electrospinning technology in an environment with a temperature of 30°C and a humidity of less than 50%. The electrospinning precursor solution obtained by S1 was sucked into a 21G 10mL syringe (with an inner diameter of about 0.5mm), placed in an electrospinning device, and aluminum foil was attached to a metal plate for electrospinning to obtain electrospinning nanofibers. The voltage of electrospinning was 15kV, the receiving distance was 10cm, and the propulsion speed of the electrospinning solution was 0.1mL / h.
[0048] S3, preparation of carbon nanofibers: The electrospun nanofibers obtained by S2 were placed in a vacuum drying oven and dried at 80°C for 12h, with a vacuum degree of 0.1Mpa. The electrospun nanofibers were then cut into 3×3cm sizes and laid flat on a porcelain boat, and then placed in a tubular furnace, with a heating rate set to 1°C / min. In an air atmosphere, the temperature was raised to 270°C and kept warm for 1h to complete pre-oxidation. Subsequently, the pre-oxidized electrospun nanofibers were placed in a tubular furnace, argon was introduced, and the temperature was raised to 900°C at a heating rate of 5°C / min for graphitization. The graphitization time was 2h to obtain unmodified carbon nanofibers (CNF).
[0049] S4, preparation of modified carbon nanofibers (CNF-PF-1): The unmodified carbon nanofibers (CNF) obtained by S3 were immersed in 50 mL K 2 FeO 4 Solution 12h (CNF and K 2 FeO 4 The mass ratio of 1:1) was 1:1), and after the first drying at 80°C, it was placed in a tube furnace, argon was introduced, and the temperature was raised to 900°C at a heating rate of 5°C / min, and calcined for 2 hours to obtain an iron-carbon mixture (Fe-based C mixture). The iron-carbon mixture was acidified and immersed in a 1.0 mol / L HCl solution to remove residual iron and iron-based compounds. After filtering, washing, and second drying, the modified carbon nanofiber (CNF-PF-1) was obtained.
[0050] Embodiment 2
[0051] Except for S4, the remaining operations of this embodiment are the same as those of the embodiment 1. The difference of S4 is that CNF and K 2 FeO 4 The mass ratio of is 1:3, and the operation of S4 is the same as that of Example 1, and finally modified carbon nanofibers (CNF-PF-3) are obtained.
[0052] Embodiment 3
[0053] Except for S4, the remaining operations of this embodiment are the same as those of the embodiment 1. The difference of S4 is that CNF and K 2 FeO 4 The mass ratio of is 1:5, and the operation of S4 is the same as that of Example 1, and finally modified carbon nanofibers (CNF-PF-5) are obtained.
[0054] Embodiment 4
[0055] Except that the mass fraction of polyacrylonitrile in the electrospinning precursor solution of this embodiment is different from that of Example 2, the rest of the operations are the same as those of Example 2. The mass fraction of polyacrylonitrile in the electrospinning precursor solution of this embodiment is 7.36%, and modified carbon nanofibers (CNF-PF-7) are finally obtained.
[0056] Embodiment 5
[0057] Except that the mass fraction of polyacrylonitrile in the electrospinning precursor solution of this embodiment is different from that of Example 2, the other operations are the same as those of Example 2. The mass fraction of polyacrylonitrile in the electrospinning precursor solution of this embodiment is 11.69%, and modified carbon nanofibers (CNF-PF-9) are finally obtained.
[0058] Comparative Example 1
[0059] Except for step S4, the remaining operations of this comparative example are the same as those of embodiment 1, wherein the specific operation of step S4 of this comparative example is as follows:
[0060] S4, preparation of modified carbon nanofibers (CNF-PF): The unmodified carbon nanofibers (CNF) obtained by S3 were immersed in a KOH solution for 12 h, dried at 80 °C, and then calcined at 900 °C in an argon atmosphere for 2 h. After washing and drying, the carbon nanofibers were immersed in FeCl 3 solution for 12 hours. 3 The molar amount of K in Example 1 2 FeO 4 The molar amount of FeCl 3 The carbon nanofibers in the solution were calcined at 900°C for 2h in an argon atmosphere to obtain an iron-carbon mixture (Fe-based C mixture). The iron-carbon mixture was acidified and immersed in a 1.0 mol / L HCl solution to remove residual iron and iron-based compounds. The modified carbon nanofibers (CNF-P-F1) were obtained after filtration, washing, and secondary drying.
[0061] Comparative Example 2
[0062] Except for step S4, the remaining operations of this comparative example are the same as those of the second embodiment, wherein the specific operation of step S4 of this comparative example is as follows:
[0063] S4, preparation of carbon nanofiber electrode (CNF-PF): The unmodified carbon nanofiber (CNF) obtained by S3 was immersed in KOH solution for 12 h, dried at 80 °C, and then calcined at 900 °C in an argon atmosphere for 2 h. After washing and drying, the carbon nanofiber was immersed in FeCl 3 solution for 12 hours. 3The molar amount of K in Example 2 2 FeO 4 The molar amount of FeCl 3 The carbon nanofibers in the solution were calcined at 900°C for 2h in an argon atmosphere to obtain an iron-carbon mixture (Fe-based C mixture). The iron-carbon mixture was acidified and immersed in a 1.0 mol / L HCl solution to remove residual iron and iron-based compounds. The modified carbon nanofibers (CNF-P-F1) were obtained after filtration, washing, and secondary drying.
[0064] Carbon nanofiber electrode performance test
[0065] 1. Morphology test of carbon nanofibers
[0066] The carbon nanofibers (CNF-PF-1, CNF-PF-3, CNF-PF-5) obtained in Examples 1 to 3 and the unmodified carbon nanofibers CNF obtained in Example 1 were tested by scanning electron microscopy (SEM). The results are as follows: Figure 2 shown.
[0067] in, Figure 2 (a) is the SEM image of the unmodified carbon nanofiber CNF obtained in Example 1, which has a diameter of about 200 nm and a relatively smooth surface; Figure 2 (b) is the SEM image of the modified carbon nanofiber CNF-PF-1 obtained in Example 1, and its morphology is similar to that of CNF; Figure 2 (c) is the SEM image of the modified carbon nanofiber CNF-PF-3 obtained in Example 2, the surface of which is relatively rough and slightly etched, which is more suitable for the modification of carbon nanofibers; Figure 2 (d) is the SEM spectrum of the modified carbon nanofiber CNF-PF-5 obtained in Example 3. 2 FeO 4 A large amount of carbon matrix in the unmodified carbon nanofibers CNF is consumed, causing the carbon nanofibers to exhibit severe deformation. Figure 2 (e) and (f) are the SEM images of the modified carbon nanofiber CNF-P-F1 obtained in Comparative Example 1 and the modified carbon nanofiber CNF-P-F2 obtained in Comparative Example 2, respectively. It can be seen that the morphology and structure of CNF-P-F1 and CNF-P-F2 are severely damaged, and the carbon nanofibers are broken. This is due to the excessively intense reaction of KOH and carbon nanofibers at high temperatures. 2 FeO 4 The reaction process of modifying carbon nanofibers is relatively mild and will not destroy the main structure of carbon nanofibers. According to the above morphology test, it can be seen that CNF and K2 FeO 4 There are three gradients of mass ratio - 1:(0.5-1.5), 1:(2-3.5) and 1:(4.5-6).
[0068] 2. Detection of phase composition
[0069] The phase compositions of the unmodified carbon nanofiber CNF, the iron-carbon mixture and the modified carbon nanofiber CNF-PF-3 in Example 2 were detected by X-ray diffractometer (XRD). Figure 3 As shown. It can be seen that a broad peak appears at 24.6° for CNF, indicating that CNF is amorphous, while a sharp peak corresponding to the (002) crystal plane of graphite carbon (JCPDS No. 00-008-0415) appears at 26.5° for CNF-PF-3, indicating that the degree of graphitization of CNF-PF-3 is significantly higher than that of CNF.
[0070] In addition, due to the residual Fe, two weak peaks appeared at 44.7° and 82.4° in CNF-PF-3, and three characteristic peaks corresponding to the standard card of Fe (JCPDS No.00-006-0696) also appeared in the iron-carbon mixture.
[0071] 3. Detection of elemental composition and carbon structure morphology
[0072] The elemental composition and carbon structure morphology of the unmodified carbon nanofiber CNF and the modified carbon nanofiber CNF-PF-3 in Example 2 were detected by X-ray photoelectron spectroscopy (XPS). Figure 4 shown. Figure 4 (a) is the full XPS spectrum of CNF and CNF-PF-3. It can be seen that both CNF and CNF-PF-3 are composed of C and O elements, and the oxygen content of CNF-PF-3 is higher than that of CNF.
[0073] Figure 4 (b) and (c) are the C1s high-resolution XPS spectra of CNF and CNF-PF-3, respectively. The peaks are fitted into five peaks, including sp 2 Carbon, sp 3 Carbon and oxygen-containing groups. 2 FeO 4 The generated Fe will sp 3 Carbon is converted to sp 2 Carbon makes CNF-PF-3 sp 2 Carbon content increases, sp 3 The carbon content is reduced. 2The increase in carbon content will lead to an increase in the graphitization degree of carbon nanofiber CNF-PF-3, and the oxygen-containing groups of CNF-PF-3 are more than those of CNF.
[0074] 4. Contact angle measurement of CNF and CNF-PF-3
[0075] The contact angles of CNF and CNF-PF-3 prepared in Example 2 were measured by a contact angle meter (JC2000D1) using the baseline ring method. The smaller the contact angle, the better the wettability of the electrolyte on the electrode surface. Figure 5 It can be seen that the contact angle of CNF-PF-3 is 112.6°, which is smaller than that of CNF (137.5°), indicating that the hydrophilicity of CNF-PF-3 is stronger than that of CNF. The increase in the hydrophilicity of CNF-PF-3 is due to the increase in oxygen-containing groups on the surface of carbon nanofibers, which is conducive to accelerating the diffusion process of the electrode reaction.
[0076] 5. Specific surface area and pore size detection
[0077] The specific surface area and pore structure of CNF and CNF-PF-3 prepared in Example 2 were tested using a specific surface area pore size analyzer. The results are as follows: Figure 6-7 As shown. Among them, Figure 6 (a) is the N of CNF and CNF-PF-3 2 Isothermal adsorption-desorption curves, N of CNF 2 The isothermal adsorption-desorption curve (black curve) shows that N 2 The adsorption amount increases with the increase of relative pressure, and there is no inflection point, which is a typical type III isothermal adsorption-desorption curve, indicating that CNF does not have a porous structure. However, the adsorption amount of CNF-PF-3 (red curve) increases rapidly with the increase of pressure, and there is a hysteresis loop between the adsorption curve and the desorption curve, which is a typical type IV isothermal adsorption-desorption curve, indicating that there are a large number of microporous structures in CNF-PF-3, which also proves that K 2 FeO 4 The modification treatment of CNF is effective.
[0078] The pore size distribution of CNF-PF-3 is as follows Figure 7 As shown in (a) in the figure, the pore size distribution range is 0.4-0.8nm, and the most probable pore size is 0.57nm. The presence of a large number of microporous structures helps to increase the surface area of carbon nanofibers. The larger specific surface area can provide more active sites that can participate in the redox reaction of the battery. The surface morphology of CNF is observed using a transmission electron microscope. Figure 6 As shown in (b), the surface morphology of CNF-PF-3 is Figure 7 As shown in (b) in .
[0079] 6. Electrochemical test
[0080] CV and EIS tests were performed using a CHI660E electrochemical instrument with a three-electrode system.
[0081] The CNF, CNF-PF-1 prepared in Example 1, the CNF-PF-3 prepared in Example 2, the CNF-PF-5 prepared in Example 3, the CNF-PF-7 prepared in Example 4 and the CNF-PF-9 prepared in Example 5 were prepared as the corresponding working electrodes to be tested one, two, three, four, five and six. The specific preparation method is as follows: 10 mg of CNF, CNF-PF-1, CNF-PF-3, CNF-PF-5, CNF-PF-7 or CNF-PF-9 was dispersed in 2 mL of DMF and ultrasonically treated for 2 h to obtain a modified carbon nanofiber dispersion. Subsequently, 50 μL of the modified carbon nanofiber dispersion was dropped onto a glassy carbon electrode (GCE) and dried at 60 ° C for 12 h to obtain the corresponding working electrode to be tested.
[0082] During the CV test, a saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, and the working electrode 1 / 2 / 3 / blank glassy carbon electrode was used as the working electrode. The electrolyte used for the negative electrode was 1.6 mol / LV 3+ +3.0mol / LH 2 SO 4 The positive electrode electrolyte is 1.6 mol / L VO 2+ +3.0mol / LH 2 SO 4 .
[0083] CV test results are as follows Figure 8 As shown in (a) and (b), it can be seen that the CV curve of GCE, i.e. the blank electrode, has no obvious redox peak, indicating that GCE is an inert electrode and has no significant effect on V 3+ / V 2+ The CV curves of the working electrode 1 (CNF), the working electrode 2 (CNF-PF-1), the working electrode 3 (CNF-PF-3), the working electrode 4 (CNF-PF-5), the working electrode 5 (CNF-PF-7) and the working electrode 6 (CNF-PF-9) all showed a pair of symmetrical redox peaks, indicating that the carbon nanofibers have a poor electrochemical activity for V 3+ / V 2+ The redox reaction is electrochemically active, and the working electrode 3 (CNF-PF-3) has the largest redox peak current and the smallest redox peak potential difference, indicating that CNF-PF-3 has the strongest electrochemical activity.
[0084] The EIS test was carried out at a polarization potential with an amplitude of 5 mV and a frequency range of 10 -1 ~10 6 Hz. The negative and positive electrode test polarization potentials are -0.45V and 0.9V respectively.
[0085] EIS test results are as follows Figure 8 As shown in (c), it is the electrochemical impedance spectroscopy (EIS) spectrum of the working electrode 1 (CNF) and the working electrode 3 (CNF-PF-3) to be tested. It can be seen that the K 2 FeO 4 The charge transfer resistance of the treated CNF-PF-3 electrode is significantly smaller than that of CNF, and CNF-PF-3 is more conducive to V 3+ / V 2+ Charge transfer in redox reactions.
[0086] 7. Detection of discharge capacity and energy efficiency
[0087] The CNF-PF-3 prepared in Example 2 was used as the positive electrode (the other electrode was CNF), the negative electrode (the other electrode was CNF), or both the positive electrode and the negative electrode were CNF-PF-3, and both the positive electrode and the negative electrode were CNF (3×3 cm) and immersed in 0.8 mol / LV 3+ +0.8mol / L VO 2+ +3.0mol / LH 2 SO 4 After being immersed in the electrolyte for 12 hours, the assembled battery was subjected to charge and discharge tests on the Blue Battery Test System. -2 Two charge-discharge cycles were performed at a current density of 100 Å to balance the electrolyte.
[0088] from Fig. 9 As can be seen in (a), the discharge capacity of the four assembled batteries decreases with the increase of current density. At all current densities, the discharge capacity of the four batteries is as follows: both positive and negative electrodes use CNF-PF-3> negative electrode uses CNF-PF-3> positive electrode uses CNF-PF-3> blank battery. The discharge capacity of the battery with CNF-PF-3 for both positive and negative electrodes is less affected by current density, that is, it shows better high current stability.
[0089] from Fig. 9 As can be seen from (b) in Figure 1, at 100 mA·cm -2When CNF-PF-3 was used for both the positive and negative electrodes, the energy efficiency of the battery reached 75.5%, which was higher than that of the battery using CNF-PF-3 at the negative electrode (71.6%), the battery using CNF-PF-3 at the positive electrode (68.0%) and the blank battery (65.6%).
[0090] The CNF-PF-3, CNF-PF-7 and CNF-PF-9 prepared in Examples 2, 4 and 5 and the CNF-P-F1 prepared in Comparative Example 1 were used as positive and negative electrodes, respectively, and immersed in 0.8 mol / LV 3+ +0.8mol / L VO 2+ +3.0mol / LH 2 SO 4 After being immersed in the electrolyte for 12 hours, the assembled battery was subjected to charge and discharge tests on the Blue Battery Test System. -2 Two charge-discharge cycles were performed at a current density of 100 Å to balance the electrolyte.
[0091] from Fig.10 It can be seen that the battery assembled with CNF-PF-3 prepared in Example 2 as both the positive and negative electrodes has a lower charging platform and a higher discharging platform, indicating that it can effectively reduce the overpotential of the battery as an electrode, thereby helping to improve the cycle stability and life of the battery.
[0092] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: the carbon nanofibers obtained by the preparation method of the present application have high graphitization characteristics and a porous structure, which is conducive to accelerating the diffusion process of the electrode reaction, and the discharge capacity is less affected by the current density, showing better high current stability and high energy efficiency. By using the carbon nanofibers of the present application, battery manufacturers can develop battery products with higher performance and longer life to meet the market demand for efficient and reliable energy storage devices.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing modified carbon nanofibers, characterized in that: The preparation method comprises: S1, dissolving polyacrylonitrile in N,N-dimethylformamide to obtain an electrospinning precursor solution; S2, performing electrospinning treatment on the electrospinning precursor solution to obtain an electrospinning nanofiber; S3, sequentially performing pre-oxidation and graphitization treatment on the electrospun nanofiber material to obtain unmodified carbon nanofibers; S4, soaking the unmodified carbon nanofibers in a K2FeO4 solution, and then sequentially performing a first drying, calcining and acidification treatment to obtain the modified carbon nanofibers.
2. The preparation method according to claim 1, characterized in that: The mass fraction of the polyacrylonitrile in the electrospinning precursor solution is 5-15%; Preferably, the dissolving temperature is 50-80°C; Preferably, the dissolution time is 2-5h; Preferably, the relative molecular mass of the polyacrylonitrile is 50,000-200,000.
3. The preparation method according to claim 1, characterized in that: The electrospinning process comprises: sucking the electrospinning precursor solution into a syringe, and performing the electrospinning on an aluminum foil attached to a metal plate through the syringe; Preferably, the inner diameter of the needle of the syringe is 0.1-1.0 mm; Preferably, the advancement speed of the syringe is 0.1-1.0 mL / h; Preferably, the receiving vertical distance of the electrospinning is 5-15 cm; Preferably, the voltage of the electrospinning is 10-18 kV.
4. The preparation method according to claim 1, characterized in that: The S3 comprises: before the pre-oxidation, vacuum drying the electrospun nanofiber material, and then pre-oxidizing in an air atmosphere; Preferably, the vacuum drying temperature is 50-90°C; Preferably, the vacuum drying time is 6-24h; Preferably, the vacuum degree of the vacuum drying is 0.05-0.1Mpa; Preferably, the pre-oxidation temperature is 240-280°C; Preferably, the pre-oxidation time is 1-3 hours.
5. The preparation method according to claim 1, characterized in that: Carrying out the graphitization in an argon atmosphere; Preferably, the temperature is raised to the graphitization temperature at a rate of 2-5°C / min; Preferably, the graphitization temperature is 700-1000°C; Preferably, the graphitization time is 2-3 hours.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the unmodified carbon nanofiber to the K2FeO4 is 1:1-5; Preferably, the unmodified carbon nanofibers are immersed in the K2FeO4 solution for 12-24 hours; Preferably, the first drying temperature is 60-90°C; Preferably, the calcination is carried out in an argon atmosphere; Preferably, the temperature is raised to the calcination temperature at a rate of 2-5°C / min; Preferably, the calcination temperature is 700-1000°C; Preferably, the calcination time is 2-3 hours.
7. The preparation method according to claim 1, characterized in that: The reagent for the acidification treatment includes a dilute hydrochloric acid solution; Preferably, the concentration of the dilute hydrochloric acid solution is 0.5-1.5 mol / L; Preferably, after the acidification treatment, filtering, washing and second drying are performed in sequence to obtain the modified carbon nanofibers.
8. The modified carbon nanofiber obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the modified carbon nanofiber obtained by the preparation method according to any one of claims 1 to 7 in electrode materials for all-vanadium redox flow batteries, characterized in that: The applications include: dispersing the modified carbon nanofibers in N,N-dimethylformamide by ultrasonic treatment to obtain a modified carbon nanofiber dispersion; The modified carbon nanofiber dispersion is coated on a glassy carbon electrode and dried to obtain the all-vanadium redox flow battery electrode material.
10. The use according to claim 9, characterized in that: The ultrasonic treatment time is 1-5h; Preferably, the concentration of the modified carbon nanofibers in the modified carbon nanofiber dispersion is 2-5 mg / mL; Preferably, the volume of the modified carbon nanofiber dispersion for the coating is 20-80 mL; Preferably, the drying temperature is 60-90°C; Preferably, the drying time is 6-24 hours.
Citation Information
Patent Citations
Method for preparing functionalized carbon material
CN106276857A
Porous carbon nanofiber electrode used for all-vanadium redox flow battery, and preparation method and application of porous carbon nanofiber electrode
CN106876721A
Iron-nitrogen co-doped porous carbon prepared by using ferrate as iron source as well as preparation method and application of iron-nitrogen co-doped porous carbon
CN114082432A
Preparing method of aligned activative carbon nanofibers using electrospinning
KR101766143B1
Cited By
Carbon fiber loaded Fe3O4 composite material, preparation method and application thereof, and method for degrading organic pollutants by electro-Fenton oxidation
CN120394010A
Carbon fiber loaded fe3o4 composite material, preparation method and application thereof, and method for electro-fenton oxidation degradation of organic pollutants
CN120394010B